2012
DOI: 10.2174/187231312801254723
|View full text |Cite
|
Sign up to set email alerts
|

Using Copper to Fight Microorganisms

Abstract: The manuscript reviews the biocidal mechanisms of copper and its current uses in the fight against transmission of health-associated (nosocomial) pathogens, foodborne diseases, dust mites loads and fungal and wound infections. The manuscript also discusses possible future applications such as filtration devices capable of deactivating contaminated blood products and breastmilk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 161 publications
(153 reference statements)
1
59
0
Order By: Relevance
“…Pillowcases, as well as socks, undergarments, linens, diapers, and a range of other consumer products embedded with copper oxide particles, are industrially produced and have been commercially available for many years now [29]. These products have been tested in numerous safety trials and found to be non-sensitizing and non-irritating [30,31].…”
Section: Test Itemsmentioning
confidence: 99%
“…Pillowcases, as well as socks, undergarments, linens, diapers, and a range of other consumer products embedded with copper oxide particles, are industrially produced and have been commercially available for many years now [29]. These products have been tested in numerous safety trials and found to be non-sensitizing and non-irritating [30,31].…”
Section: Test Itemsmentioning
confidence: 99%
“…We used copper oxide for two main reasons: (a) copper oxide is a very reactive copper compound with potent biocidal properties, which is being used successfully in many consumer, industrial and medical device products (Borkow andGabbay 2004, 2006;Borkow et al 2007Borkow et al , 2010aBorkow and Monk 2012;Borkow 2012), and (b) copper oxide is a non-soluble copper compound. Obviously in such products, it is important that the active ingredient in the product remains in the product for the life of the product; in this case that it would not be lost into the running water.…”
Section: Discussionmentioning
confidence: 99%
“…Egyptian green and did not show any and antifungal activity against all isolated fungi. Fungi were killed when exposed to higher concentrations of copper (Borkow and Gabbay, 2005;Borkow, 2012). This means that the responding of fungal strains was differed according to fungal strain and copper dose.…”
Section: -7 Effect Of Different Pigments As Antifungal Agentsmentioning
confidence: 99%